Glavkomski bolnik v operacijski sobi - Zemljič, Maša; Gračner, Bojan (Obzornik zdravstvene nege, 1984)
The paper gives a brief historical review of the surgical treatment of glaucoma at the Maribor Eye Department. Since 1977, these operations have been performed exclusively by means of advanced microsurgical techniques. The body of information which should be accessible to the operating sister before the operation is presented, as well as the preoperative management of the patient in the operating room. The characteristical features of microsurgical interventions are described.